Do Reputable University CEOs Disclose More? Evidence from Audit Fee Transparency in Indonesia - Nabilah Az-zahra Zhafira; Damara Ardelia Kusuma Wardani; Fajar Kristanto Gautama Putra (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study examines the relationship between the educational background of CEOs from reputable universities, as measured by QS World University rankings, and audit fee disclosure, a key aspect of effective corporate governance. Methods: The sample was taken from companies listed on the Indonesia Stock Exchange (IDX), totaling 3,698 firm-year observations over the period 2010-2020. Logistic regression (OLS) methods, supported by robustness tests with firm and industry fixed effects, were used to analyze the research topic. Findings: The results indicate a significant positive relationship between the CEO’s reputable educational background and audit fee disclosure. This is reinforced by robustness test results that verify the effect through Heckman Two-Stage Regression and Coarsened Exact Matching (CEM) regression tests. These results suggest that the principles of transparent and ethical leadership are more deeply ingrained in reputable universities, leading their graduates to be more motivated to disclose audit fees. Novelty: This study provides new insights into how the human capital attribute, namely reputable education, can encourage corporate financial disclosure in emerging markets. This research focuses on the role of leadership quality, as measured by educational background, and its influence on audit fee information disclosure. The study contributes to research discussing executive characteristics, corporate governance, and audit disclosure.